The capacity of trees to remove particulate matter and lead and its impact on tree health - RATNA YUNIATI; WINDRI HANDAYANI; LAELIA NUGRAHANI; ITA KHOERUNNISA; HALIMAH HALIMAH; AFIATRY PUTRIKA; NIARSI MERRY HEMELDA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Yuniati R, Handayani W, Nugrahani L, Khoerunnisa I, Halimah, Putrika A, Hemelda NM. 2024. The capacity of trees to remove particulate matter and lead and its impact on tree health. Biodiversitas 25: 2541-2551. In urban areas, common air pollutants include particulate matter (PM) and lead (Pb) particles. Plants offer a solution to mitigate both PM and Pb particles. However, PM and Pb deposition in plant leaf organs can have an impact on tree health, which can be evaluated from plant physiological aspects. A study was conducted to compare the capacity of several plant species to absorb PM and lead particles and to determine the impact of these pollutants on the physiological aspects of plants in two locations. The selected plant species were Cerbera odollam, Polyalthia longifolia, Swietenia macrophylla, and Terminalia mantaly. The four species were chosen based on their occurrence in two distinct locations: the Universitas Indonesia (UI) campus, which represents a low-pollution area, and the Bantargebang waste landfill, which represents a highly polluted area. The method employed involves using the Gravimetric Method and observing leaf morphology to evaluate the ability to capture PM, analyzing heavy metal accumulation to assess Pb particle adsorption, and examining leaf anatomy and physiology to determine tree health. Physiological aspects were observed, including chlorophyll content, carotenoid content, relative water content (RWC), and pH of leaf extract. The results showed that the highest PM deposit on plants leaf was observed in P. longifolia, followed by S. macrophylla, C. odollam, and T. mantaly. Pb analysis revealed the order of plants that accumulate Pb, from highest to lowest, is S. macrophylla>P. longifolia>C. odollam. The PM deposits significantly affected RWC (r=-0.522, p<0.01) and it affected the content of chlorophyll (r=-0.28) and carotenoids (r=-0.017). Of all the plants studied, S. macrophylla was the most impacted, with two physiological aspects affected: pigments (chlorophyll and carotenoids), and RWC. The selection of the four tree species as pollutant absorbers in Bantargebang landfill and UI Campus is appropriate, as tree health indicators, based on the analysis of leaf anatomy and physiological characteristics, detect minimal impact from environmental stress. Polyalthia longifolia (mast tree) would be the best performer among all the tree species.